ANALISIS LATIHAN KETERAMPILAN MENULIS DALAM LKS â€œWIR LERNEN DEUTSCHâ€ SEBAGAI LATIHAN TAMBAHANÂ KETERAMPILAN MENULIS BAHASA JERMAN SISWA KELAS X SEMESTER 1 - Nur Ayni, Destri (LATERNE, 2017)
Students Worksheets is one of the learning are can help students and teachers in the process of learning. Exercise selected must meet the criteria which had been determined to support the success of school tuition to the learning process better. Hence analyze exercise is needed to know the quality of teaching book used. So going to call this research is “analysis exercise skill writing in lks “wir lernen deutsch” as additional exercises learning write a language german high school students class x the first half 1”. The formulation of the research is how conformity a form of skill writing on lks “wir lernen deutsch “ based on the bernd kast ?. This study attempts to describe conformity a form of skill writing on lks “wir lernen deutsch“ based on the Bernd Kast. In this research using the kind of research descriptive qualitative the method of analysis descriptive. Data sources obtained from lks “wir lernen deutsch” by choosing exercises writing skills. Data analysis research per lektion in accordance the types of practice of writing the theory Bernd Kast. The research is as follows: 29 exercise writing skills conforming to a type bernd kast, 17 exercise at the vorbereitendeübungen, 11 exercise at the aufbauendeübungen and 1 exercise at the strukturierendeübungen. To a kind of ein modell zum schreiblehrprozess (exercise any process of writing ), kreatives und freies schreiben ( free and creative writing ) and kommunikatives, auf reale kommunikationssituationen bezogenes schreiben ( writing communicative ) is not in lks “wir lernen deutsch”. Keywords: analysis, writing skills, worksheets students